„Ty potworze dzikszy niż Cerber w Hadesie... Psie wstrętnie cuchnący, żmijowa naturo...”, czyli o odniesieniach do zwierząt w inwektywie Michała Psellosa na mnicha Sabbaitę - Garnczarska, Magdalena (Motywy fauny i flory w literaturze i kulturze, 2018)
Michael Pselllos (1018–c. 1076) was a comprehensively educated Byzantine intellectual and politician. Now he is the best known as the author of Chronicles (Χρονογραφία), but he wrote much more texts (for example about theology, rhetoric, philosophy, natural history, agriculture). One of the little-known works is his invective on monk Sabbaitam. It is not very long poem in which he used some references to animals — both domestic and mythological (for example: dog, viper, pig, dragon, Cerberus). Psellos chose insults which were based on pejorative animal appellatives. It is worth analyzing these abuses in the context of the Byzantine culture.